Geomechanical processes during underground mining proceedings of the School of Underground Mining, Dnipropetrov'k/Yalta, Ukraine, 24-28 September 2012 /: proceedings of the School of Underground Mining, Dnipropetrov'k/Yalta, Ukraine, 24-28 September 2012. (©2012) - Unknown
No abstract available